The Amiantus Program in Poland - 20 years of implementation - Beata Świątkowska (Nofer Institute of Occupational Medicine, 2020)
Background Despite the ban on the production of asbestos-containing materials, introduced in Poland over 20 years ago, new cases of asbestos-related diseases are still being recorded. Systematic control of respiratory function in people exposed to asbestos dust is, therefore, extremely important due to the biological properties of this mineral. Material and Methods The Amiantus preventive medical examination program was undertaken in 2000 to implement the legal rights of former employees of asbestos processing plants for this type of examinations. People who have ever been employed in such factories have been authorized to use preventive medical examinations for the rest of their lives. The research is continuous, spread over time and focused, in particular, on the assessment of the respiratory system. Results Since the beginning of the program, throughout 20 years of its implementation, 8329 people have been examined, including 5199 (62.4%) men for whom a total of 34 454 medical examinations have been carried out. During the program period, the percentage of diagnosed pathologies increased from 8% in 2000 to 25% in 2019. Overall, 2078 asbestos-related diseases were diagnosed among former employees of asbestos processing plants under the Amiantus Program, which accounted for 25% of this group. Among all diseases caused by exposure to asbestos, the most common were: asbestosis (1880 cases - 90.5%), lung cancer (121 cases - 5.8%) and pleural mesothelioma (77 cases - 3.7%). Diseases of pleura in the form of plaques and diffuse pleural thickening were diagnosed in 40% of the examined patients, while radiological pulmonary shadows affected over 65% of former employees of asbestos processing plants. Conclusions The Amiantus Program, thanks to the long observation period, enabled monitoring the health of former employees exposed to asbestos, and created a unique opportunity to carry out epidemiological analyzes. These studies allowed the authors to expand their knowledge of the natural history of asbestos-related diseases. Med Pr. 2020;71(5):595-601